2014
DOI: 10.1101/gad.245811.114
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete replication generates somatic DNA alterations within Drosophila polytene salivary gland cells

Abstract: DNA replication remains unfinished in many Drosophila polyploid cells, which harbor disproportionately fewer copies of late-replicating chromosomal regions. By analyzing paired-end high-throughput sequence data from polytene larval salivary gland cells, we define 112 underreplicated (UR) euchromatic regions 60-480 kb in size. To determine the effects of underreplication on genome integrity, we analyzed anomalous read pairs and breakpoint reads throughout the euchromatic genome. Each UR euchromatic region conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
114
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(122 citation statements)
references
References 51 publications
8
114
0
Order By: Relevance
“…As mentioned earlier, breakpoint clustering is regional and not limited to a specific site. Similarly, late replication and under-replication are regional properties of chromosomes, extending over hundreds of kilobases (Belyaeva et al 2012;Yarosh and Spradling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, breakpoint clustering is regional and not limited to a specific site. Similarly, late replication and under-replication are regional properties of chromosomes, extending over hundreds of kilobases (Belyaeva et al 2012;Yarosh and Spradling 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Glaser et al (1992) reported evidence the forks do not build up in the transition zones between euchromatin and heterochromatin. Yarosh and Spradling (2014) analyzed whole-genome sequence from salivary glands, and found numerous deletions spanning zones of underreplication. They concluded that blocked forks break,…”
Section: Repair Of Damage Encountered During Replicationmentioning
confidence: 99%
“…Consistent with S phase resets, polytene cells in Dipterans generally show "underreplication" of satellite-rich regions of centromeric heterochromatin, whereas Drosophila and some other higher Dipteran species also underreplicate-specific euchromatic regions that normally duplicate late in S phase (Gall et al 1971;Hammond and Laird 1985;Karpen and Spradling 1990;Spradling 1993;Moshkin et al 2001;Belyakin et al 2005;Nordman et al 2011;Yarosh and Spradling 2014). Drosophila euchromatic unfinished replication (UR) regions were originally characterized in the larval salivary gland, but most of the same major regions undergo UR in other polytene tissues examined, including larval midgut, larval fat body, and adult ovary (Nordman et al 2011;Yarosh and Spradling 2014).…”
mentioning
confidence: 91%